Housing With Care for Older People: A Scoping Review Using the CASP Assessment Tool to Inform Optimal Design. (October 2022) - Jung, Suyee; Uttley, Lesley; Huang, Junjie
Objective: The purpose of this scoping review is to synthesize and map available evidence on the design of "housing with care" (HWC) schemes to inform design decisions built on objective data from previous research, which is key to ensuring such schemes are fit for purpose for older people. Background: HWC is becoming increasingly recognized as a model for developing housing schemes for older people and balances independent living with elevated levels of care. However, as this scheme is still relatively novel, there are currently no established theoretical frameworks to inform design. Methods: Scoping review, thematic analysis, and mapping methods were used to comprehensively search for and synthesize evidence that links design with assessments of quality-of-life data for HWC schemes. Study findings for each included paper were subject to data extraction for inductive analysis, and the quality of each study was assessed using a modified critical appaisal skills programme (CASP) checklist. Results: Our searches yielded 821 unique references, of which 18 unique articles met the inclusion criteria. The outcomes of interest were the design considerations or features in HWC schemes and their impact on the residents. The main themes identified were related to design element, accessibility, maneuverability, views, design procedure, and quality of life (QOL). Further subthemes identified across papers were identified to create a comprehensive map of the key features to consider in designing HWC schemes. Conclusion: This review provides an initial framework for designers and architects to (1) understand the effect of each design element of HWC and (2) inform design to ultimately improve the QOL of aged people.